Internalisasi Etika Ekologi melalui Experiential Learning Berbasis DAS dalam Mendukung Edukasi Mitra Sungai - Vemi Eka Hastanti; Sinta Sinta; Fenty Fauziah; Fitriansyah Fitriansyah (JPM: Jurnal Pengabdian Masyarakat, 2026)
The Karang Mumus sub-watershed in Samarinda City faces ecosystem degradation due to domestic waste pollution, riparian land conversion, and generally low urban ecological literacy. As future decision-makers in the management sector, graduate management students require direct exposure to urban ecological realities so their understanding extends beyond theoretical discourse. This community engagement activity aims to internalize watershed-based ecological values, strengthen students' ecological literacy through experiential learning, and build an ecological ethic as a foundation for eco-literate leadership. The method applied is a participatory educative approach implemented through four stages field observation, semi-structured interviews with a community resource person, focused group discussion, and direct experiential learning involving 24 students of the Master of Management Program at Universitas Muhammadiyah Kalimantan Timur on 10 May 2026, accompanied by Mr. Misman, initiator of the Karang Mumus River School community (GMSS-SKM). The results show a shift in students' perspectives from viewing the river merely as a physical channel toward a holistic understanding of the watershed as a catchment system connected to domestic activities. Students gained new understanding of simple, locally-sourced wastewater treatment concepts, the ecological function of riparian vegetation, the impact of pesticide residues on water quality, and the distinction between "visual green" and "ecological green." The activity concluded with hands-on tree planting as a concrete manifestation of the ecological values learned. This activity serves as an ecological trigger that lays a cognitive and motivational foundation for students to integrate sustainability perspectives into their future managerial practices and academic research.